Correction: Karaköse, M.; Yücel, Ö. Predictive Modeling of the Hydrate Formation Temperature in Highly Pressurized Natural Gas Pipelines. Energies 2024, 17, 5306 - Mustafa Karaköse; Özgün Yücel (Energies)
Error in Affiliation [...]